Disrupting health professions education research: a guide to critical reflexive praxis during research planning - Sims, DA; Saunders, P (Taylor and Francis Group, 2025)
Research is never truly neutral; all research is inherently subjective because it is shaped by who conducts it, how they think, and the systems they operate within. Paradoxically, despite reflexivity’s critical intent – a practice for recognising and addressing researcher influence – it too often becomes a superficial checkbox exercise that fails to meaningfully challenge deeper structural and systemic inequities. As a result, Health Professions Education (HPE) research often reinforces global power imbalances, privileging Western perspectives while excluding knowledge from the Global South and marginalised communities. This article advocates for Critical Reflexive Praxis (CRP), an approach grounded in Critical Theory, that combines self-reflection with deliberate action to disrupt power dynamics and promote equity in research. CRP extends beyond traditional reflexivity by interrogating and transforming the underlying structures that shape knowledge production and dominant research practice. By adopting CRP, researchers can challenge entrenched hierarchies, include and amplify marginalised perspectives, and create research that fosters meaningful social transformation. This article offers practical guidelines for enacting CRP across individual, interpersonal, local, and global levels during HPE research planning, paving the way for more equitable and impactful contributions to HPE and beyond.